1962
DOI: 10.1677/joe.0.0240435
|View full text |Cite
|
Sign up to set email alerts
|

URINARY EXCRETION OF ANDROST-16-EN-3α-OL LEVELS IN NORMAL SUBJECTS, AND EFFECTS OF TREATMENT WITH TROPHIC HORMONES

Abstract: Data are presented on the urinary excretion of androst-16-en-3\g=a\-olby normal human subjects over the age span 4-86 years. The figures range from < 100 to 2630 \g=m\g./24 hr. in males, and < 100 to 1100 \g=m\g./24 hr. in females, the mean for men of 16-45 years being nearly three times that for women of the same age.The effect on urinary androstenol and 17-oxosteroids of human chorionic gonadotrophin (HCG) and of corticotrophin (ACTH) have been compared in three normal young men and two women. Marked elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1963
1963
1994
1994

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…It is extremely unfortunate that the 2 men chosen as experimental subjects in this study excreted very low amounts of urinary 3a-androstenol when com pared with the average established for men of the same age range in other investigations (Brooksbank, 1962;Brooksbank and Gower, 1970). This low urinary output of 3a-androstenoi is parallelled by low blood 3a-androstenol concentrations, in comparison with the mean established for men by the assay used, and by the lower BPR of 3a-androsteno!…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It is extremely unfortunate that the 2 men chosen as experimental subjects in this study excreted very low amounts of urinary 3a-androstenol when com pared with the average established for men of the same age range in other investigations (Brooksbank, 1962;Brooksbank and Gower, 1970). This low urinary output of 3a-androstenoi is parallelled by low blood 3a-androstenol concentrations, in comparison with the mean established for men by the assay used, and by the lower BPR of 3a-androsteno!…”
Section: Discussionmentioning
confidence: 50%
“…These metabolic parameters were studied in both male and female subjects since sex differences had already been shown in urinary excretion rates of androstenol, tire male rate being about four times the female rate (Brooksbank, 1962;Brooksbank and Gower, 1970). The conversion of androstadienone to dihydroxylated derivatives had also been shown to differ in male and female subjects (Brooksbank et al, 1972a).…”
Section: Introductionmentioning
confidence: 99%
“…(Brooksbank & Haslewood, 1961). Intramuscular injection of the compound leads to low recoveries in the urine, of the order of 10 % (Brooksbank, 1962). This may very well mean a secretion rate of androstenol or its precursor as high as 10 mg./24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary ll-deoxy-17-oxosteroids are often termed the 'androgen metabolites', but the amounts of these compounds found in the urine do not always bear a very close relationship to clinical signs of an excessive androgenic stimulus in women (Brooksbank, 1961). Recently, Dorfman (1962) has suggested that the clinical signs of hyperandrogenicity correlated better with blood levels of testosterone as deter¬ mined by the method of Finkelstein, Forchielli & Dorfman (1961) and that this com¬ pound may be the most important androgen in women.…”
Section: Introductionmentioning
confidence: 99%
“…Deshalb schien es uns notwendig, zunächst den Metabolismus von freiem Te stosteron bei normalen und hirsuten Frauen vergleichend zu unter suchen; denn alle bisherigen diesbezüglichen Studien wurden unseres Wissens stets m it einem Ester -meist dem Propionat -und nur bei nicht hirsuten Frauen durchgeführt [4,5,6], Von besonderem Interesse war für uns auch die Ausscheidung des wenig bekannten Urinsteroids 16-Androsten-3a-ol ( Fig. 1) vor und nach einer Testosteronbelastung zu studieren; dies um so m ehr, weil die Befunde von Brooksbank und Hasleivood [7,8] …”
unclassified